Coupled cantilever sensors for bio applications-a comparitive study - N.SIDDAIAH; G.R.K PRASAD; D.V.RAMA KOTIREDDY; Dr. B. MAHENDRAN (International Journal of Pharma and Bio Sciences, 2017)
In last decade, arrival of Micro-electromechanical systems (MEMS) have been immense and ever growing. In this paper, we have proposed a new T-shape and disc shape MEMS based triple coupled Cantilever sensors. We have designed and simulated a T-Shape and disc shape MEMS based triple coupled cantilever sensor made up of P-Silicon (Polycrystalline, Lightly doped) .Both coupled sensors have same effective area. The simulation results like displacement, Eigen-frequency, surface stress, temperature, measurements of the both triple coupled cantilever sensors are compared .This paper gives relative study of two different shape coupled micro-cantilevers.